Environmental Issues in South African Broadcast Media: A Content Analysis of Coverage, Framing, and Source Representation - Mokoena, Zanele; Nkosi, Lindiwe (Asian Journal of Media and Communication, 2024)
This study explores the coverage of environmental issues in South African broadcast media, focusing on patterns, frames, and source representation, applying agenda-setting and framing theories. Employing a content analysis methodology, 360 prime-time news segments from three major broadcasters – SABC, eNCA, and Newzroom Afrika – were analyzed between July 2023 and June 2024. The findings revealed that climate change dominates coverage, accounting for 32% of environmental reporting, followed by natural disasters (21%) and water issues (17%). Economic and policy frames were the most prevalent, highlighting financial impacts and regulatory measures, while health perspectives were underutilized. Government sources were cited most frequently (44%), with limited representation of scientists, NGOs, and local communities, which comprised only 10% of sources. Coverage exhibited a mixed tone, balancing optimism about solutions with urgency about challenges. Despite a focus on global narratives, local environmental issues and grassroots perspectives were underrepresented, indicating a disconnect between media reporting and the lived experiences of South Africans. The study underscored the need for more inclusive and diverse coverage, advocating for the integration of scientific insights and community voices. These findings offered practical implications for media practitioners, policymakers, and environmental communicators, emphasizing the importance of balanced reporting to foster public engagement and informed policy discourse. This research provided a foundation for future studies on environmental journalism, especially in the context of developing countries, and highlighted the potential for media to act as a catalyst for environmental awareness and action.